INFLUENCE OF CULTURE MEDIUM COMPOSITION AND EXPLANT TYPE ON MICROPROPAGATION OF THE ROOTSTOCK Prunus sp. ‘GxN-9’ - RADMANN, Elizete Beatriz; BIANCHI, Valmor João; SOUZA, Tatiane Medeiros; FACHINELLO, José Carlos; de OLIVEIRA, Roberto Pedroso (Scientia Agraria, 2009)
The objective of the present work was to study the composition of different culture medium, BAP concentration and explants types on in vitro multiplication of the rootstock ‘GxN-9’, like the influence of this factors in the vitrification. Basal explants cultivated in QL and WPM medium had the better results regarding shooting percentage (80%). The shoot number per explants was also higher with basal explants when cultivating in QL medium (3 shoot a explant). The medium QL and WPM allowed better growth performance of formed shoots to both explants types. Nevertheless, basal explants cultivated in QL medium had 55% of vitrification, whereas explants from WPM medium did not show this abnormality. The lower level of salt concentration with 0.5 mg dm-3 BAP reduced vitrification, promoting an increase in shoot growth without affecting formation rates.